The Effect of Workplace Spirituality and Ethical Climate on the Corporate Sustainability Performance of Retail Chain Stores in Thailand - Jermsittiparsert, Kittisak; Sangperm, Nuanluk; Siriattakul, Parinya (International Journal of Psychosocial Rehabilitation, 2019)
The recent literature in management has highlighted the significant and prominent role of workplace spirituality in enhancing organizational performance. However, the literature provides little attention towards the interdependency of internal, i.e., workplace spirituality and external factors, i.e., the ethical climate in developing and enhancing corporate sustainability performance. Therefore, to fill this gap, the present study was conducted with an aim to assess the direct effect of i) workplace spirituality on ethical climate, ii) ethical climate on corporate sustainability performance and indirect effect of iii) ethical climate in the relationship between workplace spirituality and corporate sustainability performance. By collecting the data from 326 employees of 63 retail stores in Thailand, the study finds found empirical backing to support several hypotheses. First, the workplace spirituality is proved to be an important antecedent of ethical climate. Second, the corporate sustainability is significantly predicted by ethical climate. Finally, the ethical climate mediates between the relationship of workplace spirituality and corporate sustainability performance. The study also possessed the practical implications for owners and managers of retail stores in Thailand